(untitled) (Bangladesh Journal of Child Health, 2013)
Background : Gastroschisis is a congenital abdominal wall defect with high mortality in developing countries. In developed countries their survival rate is more than ninety percent. This is due to appropriate information about the disease and adequate management plan. We have a good number of patients, but majority of us are lacking appropriate information about this disease. Objectives: This study was done to give some information to our medical personals about this disease and to evaluate the out come of gastroschisis in relation to birth weight, age of neonate and procedure of closure of the defect. Methodology: This prospective observatinal study was done in the surgery department of Dhaka Shishu Hospital (DSH) in a period of two years. All gastroschisis patients admitted during this period were enrolled and their mortality were analyzed in relation to weight, age and operative procedure. Minimal intervention management of gastroschisis (MIMG) were performed in suitable cases. Results: A total of 32 patients were admitted. Mortality were significantly high among the VLBW babies than babies whose birth weight > 1500 gm (88.9% vs17.4%) and those who were admitted after 24 hours of age than who admitted before 24 hours of age (66.7% vs26.1%). Overall survival rate was 62.5% and after surgery 71.5%. Conclusion: Gastroschisis is not rare in our population. Birth weight, early hospitalization with primary closure as early as possible, proper selection of patient for MIMG effect outcome. Adequate supportive measures like TPN, neonatal ICU and information about the disease will further increase the survival rate. DOI: http://dx.doi.org/10.3329/bjch.v36i3.14276 BANGLADESH J CHILD HEALTH 2012; VOL 36 (3) : 133-138